Mutation screening of the SLC26A4 gene in a cohort of 192 Chinese patients with congenital hypothyroidism - Chunyun Fu (Archives of Endocrinology and Metabolism, 2016)
ABSTRACT Objective Pendred syndrome (PS) is an autosomal recessive disorder characterised by sensorineural hearing loss and thyroid dyshormonogenesis. It is caused by biallelic mutations in the SLC26A4 gene encoding for pendrin. Hypothyroidism in PS can be present from birth and therefore diagnosed by neonatal screening. The aim of this study was to examine the SLC26A4 mutation spectrum and prevalence among congenital hypothyroidism (CH) patients in the Guangxi Zhuang Autonomous Region of China and to establish how frequently PS causes hearing impairment in our patients with CH. Subjects and methods Blood samples were collected from 192 CH patients in Guangxi Zhuang Autonomous Region, China, and genomic DNA was extracted from peripheral blood leukocytes. All exons of the SLC26A4 gene together with their exon-intron boundaries were screened by next-generation sequencing. Patients with SLC26A4 mutations underwent a complete audiological evaluation including otoscopic examination, audiometry and morphological evaluation of the inner ear. Results Next generation sequencing analysis of SLC26A4 in 192 CH patients revealed five different heterozygous variations in eight individuals (8/192, 4%). The prevalence of SLC26A4 mutations was 4% among studied Chinese CH. Three of the eight were diagnosed as enlargement of the vestibular aqueduct (EVA), no PS were found in our 192 CH patients. The mutations included one novel missense variant p.P469S, as well as four known missense variants, namely p.V233L, p.M147I, p.V609G and p.D661E. Of the eight patients identified with SLC26A4 variations in our study, seven patients showed normal size/location of thyroid gland, and one patients showed a decreased size one. Conclusions The prevalence of SLC26A4 pathogenic variants was 4% among studied Chinese patients with CH. Our study expanded the SLC26A4 mutation spectrum, provided the best estimation of SLC26A4 mutation rate for Chinese CH patients and indicated the rarity of PS as a cause of CH.